Prenatal diagnosis of mucopolysaccharidosis type I on hepatosplenomegaly and coarse features: a case-report - Maxime Agranier; Florence Demurger; Christele Dubourg; Jerome Fromageot; Anne-Sophie Cabaret Dufour; Erika Launay; Magalie Gournay; Charles Lefèvre; Roseline Froissart; Magali Pettazzoni; Paul Rollier (BMC Pregnancy and Childbirth)
Abstract Background Mucopolysaccharidosis type I (MPS I - IDUA gene) is a rare autosomal recessive lysosomal storage disorder. Clinical symptoms, including visceral overload, are progressive and typically begin postnatally. Descriptions of hepatosplenomegaly associated with lysosomal pathology are uncommon during the prenatal period. The most prevalent etiologies are infections, anemia, and neoplasms. Case presentation A pregnant woman at 26.5 gestational weeks was referred to our center for fetal ultrasound findings of hepatosplenomegaly, distinct facial features, and liver, spleen and thymus echogenic spots. Whole exome sequencing after amniocentesis identified two likely pathogenic IDUA gene variants (in trans), raising suspicion of a diagnosis of MPS I. MPS I was confirmed by the deficiency of α-L-iduronidase activity in amniotic cells. A medical pregnancy termination was carried out due to the severe prognosis. After termination of pregnancy, external examination of the fetus confirmed hepatosplenomegaly and coarse dysmorphic features. Conclusion Lysosomal storage diseases (LSD) are a rare cause of prenatal hepatosplenomegaly, but this has not been described in MPS I according to our literature search. The genetic variants identified in this case prompted early diagnosis through genome-wide studies. This rare presentation of MPS I highlights the expanding role of genomic analyses in diagnosing conditions during pregnancy.